Some Issues of Federalism and Constitutionality – Experiences of the European Union and Serbia - Tubic, Bojan (Federalism as the Future of the Diverse EU?, 2025)
This Chapter deals with different aspects of federalism observed in the European Union and in the Republic of Serbia. The latter has changed its statehood several times in the last century and was mainly included as a part of complex states and federations after the Second World War. The experience of Serbia and states which it was a part of is similar to that of the EU. Although the method of creation was not the same, the structure, some aspects of decision-making and others factors are very similar. Some experiences from these states can be used in the study of the European Union. Also, the issue of human rights has a significant role in the constitutional system of every country. Human rights are regulated in a similar manner in the EU and the Republic of Serbia, and with future membership on the horizon there will be a stronger interaction between the two legal systems. There is a possibility that the EU joins the European Convention on Human Rights which could improve human rights protection in this international organisation. Moreover, the questions of primacy of EU law and judicial review are at the core of constitutionalism. The special, sub-national character of the European Union includes the supremacy of EU law over that of member states, like in a federation and also in the federations in which Serbia was a part of. Also, a judicial review of its acts is possible before the Court of the EU, which has substantial jurisprudence in this field regarding the direct and indirect review of the European Union’s acts. With these characteristics of its legal system, the European Union is moving toward a state but it is still one sui generis international organisation. Keywords: federalism, constitutionality, European Union, human rights, judicial review.